The evolutionary history of "suboptimal" migration routes - Bensch Staffan; Caballero-López Violeta; Cornwallis Charlie K; Sokolovskis Kristaps (Cell Press, 2025)
Migratoriness in birds is evolutionary labile, with many examples of increasing or decreasing migration distances on the timescale of modern ornithology. In contrast, shifts of migration to more nearby wintering grounds seem to be a slow process. We examine the history of how Palearctic migratory landbirds have expanded their wintering ranges to include both tropical Africa and Asia, a process that has involved major shifts in migratory routes. We found that species with shorter migration distances and with resident populations in the Palearctic more often winter in both Africa and Asia. Our results suggest that changes in wintering grounds are not by long-distance migrant populations per se, but through historic intermediate populations that were less migratory from which long-distance migration evolved secondarily. The failure of long-distance migrants to shift migration direction to more nearby winter quarters indicates that major modifications to the migratory program may be difficult to evolve.